Sistem Informasi Pengelolaan Lapangan Bulu Tangkis “Wirda Buana” Berbasis Java Netbean - Kholifah, Amelia Nur; Valentino, V.H.; Prasetya, Rudi (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
This study aims to design a management system on the Wirda Buana badminton court into an applied system in order to simplify the process of recording field rentals. The main problem in this research is the management process which is currently still manual. The rental process is carried out by recording the file of prospective tenants in a book, making it difficult for officers to copy the file of renting customers. Payment transaction that are only recorded in the book result in frequent miscalculations and make the reporting not on time. The file of this study were obtained from the results of observations and interviews. In the process consists of planning, analysis, design and implementation of the system. The results of this study are an information system for badminton court management based on java netbeans with this information system, it is expected to make it easier for admins to manage field rental data as well as owners in monitoring the course of field rental activities.